Short but Weak: The Z‐DNA Lone‐Pair⋅⋅⋅π Conundrum Challenges Standard Carbon Van der Waals Radii. (15th July 2020) - Kruse, Holger; Mrazikova, Klaudia; D'Ascenzo, Luigi; Sponer, Jiri; Auffinger, Pascal
Abstract: Current interest in lone‐pair⋅⋅⋅π (lp⋅⋅⋅π) interactions is gaining momentum in biochemistry and (supramolecular) chemistry. However, the physicochemical origin of the exceptionally short (ca. 2.8 Å) oxygen‐to‐nucleobase plane distances observed in prototypical Z‐DNA CpG steps remains unclear. High‐level quantum mechanical calculations, including SAPT2+3 interaction energy decompositions, demonstrate that lp⋅⋅⋅π contacts do not result from n→π* orbital overlaps but from weak dispersion and electrostatic interactions combined with stereochemical effects imposed by the locally strained structural context. They also suggest that the carbon van der Waals (vdW) radii, originally derived for sp 3 carbons, should not be used for smaller sp 2 carbons attached to electron‐withdrawing groups. Using a more adapted carbon vdW radius results in these lp⋅⋅⋅π contacts being no longer of the sub‐vdW type. These findings challenge the whole lp⋅⋅⋅π concept that refers to elusive orbital interactions that fail to explain short interatomic contact distances. Abstract : Short lp⋅⋅⋅π contacts in Z‐DNA steps result from a combination of compression effects induced by a highly strained structural context and an effective van der Waals (vdW) radius of a guanine sp 2 carbon atom that is estimated to be much smaller than the standard 1.70 Å vdW radius of sp 3 carbons generally used to assess the sub‐vdW character of these interactions.